Analisis Percepatan Durasi Proyek Dengan Menggunakan Metode Crashing - Pramana, I Dewa Made Agung; Siregar, Amril Ma'ruf; Herianto, Dwi (Universitas Lampung, 2020)
There are possible problems arise during construction of project that can cause delays. Delays can cause losses in the form of fines, overhead costs, additional salaries and rental tools and other. To overcome the problems, there are some ways to achieve project completion in due time. The purpose of this study was to analyze the acceleration of the project duration by utilizing crashing method and its impact on project cost. The object of the case study was the construction of Lampung Regional Police Headquarter. The scenario utilized was increased the number of workers by 35% and the added working hours by four hours. The results show by increasing the number of workers across eleven project activities, the project duration was crashed to 252 days or two days earlier than the scheduled time and the project cost was decrease to Rp. 23,964,647,646.00 or 0.908% lower than the scheduled cost. The results also show by adding four more working hours across ten project activities, the project duration was crashed to 253 days or one day earlier than the scheduled time and the project cost was decreased to Rp. 23,995,417,215.00 or 0.781% lower than the scheduled budget. Keywords: Project Acceleration, Crashing method, increase of the number of workers, the addition of working hours